病原真菌Candida glabrataにおけるElm1の抗真菌薬感受性および病原性への関与 - 伊藤, 裕也 (Springer Nature, 2020)
Nagasaki University (長崎大学) 博士(医学) Elm1 is a serine/threonine kinase involved in multiple cellular functions, including cytokinesis, morphogenesis, and drug resistance in Saccharomyces cerevisiae; however, its roles in pathogenic fungi have not been reported. In this study, we created ELM1-deletion, ELM1-reconstituted, ELM1-overexpression, and ELM1-kinase-dead strains in the clinically important fungal pathogen Candida glabrata and investigated the roles of Elm1 in cell morphology, stress response, and virulence. The elm1Δ strain showed elongated morphology and a thicker cell wall, with analyses of cell-wall components revealing that this strain exhibited significantly increased chitin content relative to that in the wild-type and ELM1-overexpression strains. Although the elm1Δ strain exhibited slower growth than the other two strains, as well as increased sensitivity to high temperature and cell-wall-damaging agents, it showed increased virulence in a Galleria mellonella-infection model. Moreover, loss of Elm1 resulted in increased adhesion to agar plates and epithelial cells, which represent important virulence factors in C. glabrata. Furthermore, RNA sequencing revealed that expression levels of 30 adhesion-like genes were elevated in the elm1Δ strain. Importantly, all these functions were mediated by the kinase activity of Elm1. To our knowledge, this is the first report describing the functional characterization of Elm1 in pathogenic fungi. 長崎大学学位論文 学位記番号:博(医歯薬)甲第1275号 学位授与年月日:令和2年9月2日 Author: Yuya Ito, Taiga Miyazaki, Yutaka Tanaka, Takashi Suematsu, Hironobu Nakayama, Akihiro Morita, Tatsuro Hirayama, Masato Tashiro, Takahiro Takazono, Tomomi Saijo, Shintaro Shimamura, Kazuko Yamamoto, Yoshifumi Imamura, Koichi Izumikawa, Katsunori Yanagihara, Shigeru Kohno & Hiroshi Mukae Citation: Scientific Reports, 10, art.no.9789; 2020 Nagasaki University (長崎大学), 博士(医学) (2020-09-02) doctoral thesis